ANALISIS DUKUNGAN PERUSAHAAN TERHADAP KESIAPAN KARYAWAN MENGHADAPI PERUBAHAN PADA CV. NIKI HARUM SEMARANG - Henny, Henny (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
High quality human resources are highly expected by companies today to help them achieve their goals. Knowledgeable and reliable personnel will be very beneficial for the company. The purpose of this study is to gain a better understanding of how the company supports employee readiness to face change at CV. Niki Harum Semarang. In this study, the author applies theory and experience in the field of Organizational Behavior, especially those related to changes in the organization and company performance. This study aims to provide input/knowledge to employees of CV. Niki Harum Semarang in responding to positive changes that occur within the organization/company so that they can take a positive attitude if stress arises at work. This study uses a method known as systematic random sampling, and is conducted with a questionnaire. An in-depth regressive analysis strategy is used in this research investigation. The results of this study indicate that employee readiness to face change has a positive and statistically significant effect on company performance. It is highly recommended that companies meet employee needs in facing change so that it has a positive and statistically significant effect on employee readiness to face change to maintain and improve good company performance and will support the company in achieving its main goal, namely company profit.